Developmental programming: Adipose depot-specific changes and thermogenic adipocyte distribution in the female sheep. (1st March 2020) - Puttabyatappa, Muraly; Ciarelli, Joseph N.; Chatoff, Adam G.; Singer, Kanakadurga; Padmanabhan, Vasantha
Abstract: Prenatal testosterone (T)-treated female sheep exhibit an enhanced inflammatory and oxidative stress state in the visceral adipose tissue (VAT) but not in the subcutaneous (SAT), while surprisingly maintaining insulin sensitivity in both depots. In adult sheep, adipose tissue is predominantly composed of white adipocytes which favor lipid storage. Brown/beige adipocytes that make up the brown adipose tissue (BAT) favor lipid utilization due to thermogenic uncoupled protein 1 expression and are interspersed amidst white adipocytes, more so in epicardiac (ECAT) and perirenal (PRAT) depots. The impact of prenatal T-treatment on ECAT and PRAT depots are unknown. As BAT imparts a metabolically healthy phenotype, the depot-specific impact of prenatal T-treatment on inflammation, oxidative stress, differentiation and insulin sensitivity could be dictated by the distribution of brown adipocytes. This hypothesis was tested by assessing markers of oxidative stress, inflammation, adipocyte differentiation, fibrosis and thermogenesis in adipose depots from control and prenatal T (100 mg T propionate twice a week from days 30–90 of gestation) -treated female sheep at 21 months of age. Our results show prenatal T-treatment induces depot-specific changes in inflammation, oxidative stress state, collagen accumulation, and differentiation with changes being more pronounced in the VAT. Prenatal T-treatment also increased thermogenic gene expression in all depots indicative of increased browning with effects being more prominent in VAT and SAT. Considering that inflammatory and oxidative stress are also elevated, the increased brown adipocyte distribution is likely a compensatory response to maintain insulin sensitivity and function of organs in the proximity of respective depots. Highlights: Prenatal testosterone excess programs adipose depot-specific changes. Depot-specific changes include negative/positive mediators of insulin sensitivity. Prenatal testosterone excess increases thermogenic markers in all adipose depots. Increase in thermogenesis may underlie preserved VAT and SAT insulin sensitivity.